Redesign Website Mitra Mapan Mulia Untuk Meningkatkan User Experience Menggunakan Metode Lean Ux - Isdriani Isdriani; Bayu Setiawan (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
This research applies the Lean UX approach in redesigning the Mitra Mapan Mulia website with the purpose of enhancing user experience. The Lean UX method is used as a responsive and efficient approach to designing solutions that are more user-focused. Data was collect using interview, literature study and observation methods. The research subjects were state-owned companies and MSMEs. The results showed that there was an improvement in user experience, with performance parameters including navigation time, information clarity, and engagement level. Evaluation results from users involved in prototype testing showed a positive response to design changes, and the use of Lean UX methods provided advantages in accelerating the design process and increasing user satisfaction. This research contributes to the practical understanding and effectiveness of Lean UX in the context of website redesign to achieve the goal of improving user experience